PENINGKATAN KUALITAS PEMBELAJARAN KIMIA BAHAN ALAM MELALUI METODE PENGENALAN POLA - ., Nurbaity (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Improving the Quality of the Natural Chemical Substance Lesson through the Pattern Recognizing Method. This study aims to improve the quality of the natural chemical substance lesson through the pattern recognizing method. This study was an action research study consisting of two cycles, each of which involved three meetings. The first cycle presented the polyketide topic and the second cycle the terpenoid topic. The instruments were questionnaires, observation sheets, and evaluation sheets. The final stage of the second cycle showed that: 1) the quality of the assignments involving natural substances and the number of chemical found in the references improved, which made it easier to move to further steps, 2) the students’ activities and participation increased, indicated by the group presentation in which each group had a chance to raise questions, 3) the quality and quantity of questions, especially high level ones, increased, and all of them were written and submitted, and 4) the students’ learning achievement improved, indicated by the percentage of students achieving scores above 60 (84%). Keywords: natural chemical substance, pattern recognizing method